Screening, characterization and calcium-binding properties of novel yak milk peptides - Bo Zhao; Xinyi Li; Yanping Guo; Wenting Li; Torkun Mamet; Nidhi Bansal (International Dairy Journal, 2026)

Three birds with one stone: a disintegrable fertilizer with rapid fertilization, controlled-loss and detoxification - Xianghai Kong; Chen Sun; Ziyu You; Wanji Zhu; Xinxin Zhai; Yuhao Wang; Yan Wang; Weijian Zhang; Kaimin Zhu; Xiaoshuang Han; Pan Zhao; Yanping Zhu; et al. (Desalination, 2026)

Genome-resolved characterization of candidate thermotolerance traits and predicted protein conformational behavior in Calditerricola during hyperthermophilic composting of organic wastes - Xu Li; Zhengnan Zhu; Youzhao Wang; Yanping Zhang; Xiaoyan Dang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Feng Ma; Liying Hao; Tong Zhu (Bioresource Technology, 2026)

Effective strategy for simultaneous removal of Congo red and Cr(VI) by ferroan brucite - Shifeng Zhao; Xin Fan; Fengzhu Lv; Yanping Zhao; Yuli Cui (Journal of Water Process Engineering, 2026)

Waste soy milk-derived biodegradable seed coating agent: Synthesis, growth-promotion and drought resistance - Dongqing Cai; Cun Jiang; Bingbing Fu; Shihu Shu; Dongfang Wang; Pan Zhao; Yanping Zhu (Journal of Environmental Chemical Engineering, 2026)

Evolution of fine structure and pasting properties in wheat starch during medium-high-temperature Daqu fermentation - Zhenbing Ma; Yuanyuan Tian; Dong Zhao; Lihua Zhao; Jia Zheng; Jian Su; Yanping Lu; Yi Ma (Food Research International, 2026)

Potential of biofortification with tissue-adhesive exopolysaccharide-producing Lactiplantibacillus plantarum to fine-tune microstructure, stabilize texture and color, and enrich flavor of radish Paocai during fermentation - Yuli Huang; Haimei Lai; Yali Wang; Jiaqi Liu; Mengting Liu; Yanping He; Lihong Ge; Nan Zhao (Food Bioscience, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

Inflammation-targeted bioactive SiMo glass-ceramic nanozymes for adaptive and sequential infection-impaired wound repair through precise immunoregulation and antiinfection - Jing Tian; Yanzi Zhao; Yanping Zuo; Xiaochen Su; Long Zhang; Weipeng Qiang; Zuhao Zhang; Minhui Ai; Houjin Zhuang; Qian Huang; Meng Luo; Bo Lei (Chemical Engineering Journal, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Salinity reduces cadmium bioavailability and toxicity in the Oryzias melastigma: Evidence from fish exposure and cell-based ion-competition assays - Zhongdian Dong; Jinghua Wang; Haozhong Tian; Jiahao Gao; Yue Liu; Nengneng Ding; Yiqing Yuan; Guohua Zhu; Xiaomin Zhao; Zailiang Li; Ning Zhang; Yanping Zhang; et al. (Marine Pollution Bulletin, 2026)

Habitat-dependent and asymmetric drivers of spectral diversity–biodiversity relationships in temperate grasslands - Yi Zhang; Yujin Zhao; Zhisheng Wu; Yanping Zhao; Wenhe Chen; Weifang Li; Zhaoju Zheng; Fei Li; Yongfei Bai (Remote Sensing of Environment, 2026)

Structure-reactivity relationship of monomeric flavan-3-ols in forming ethyl-linked anthocyanin pigments: an integrated experimental and computational study - Xu Zhao; Yanping Guo; Zihao Ye; Xinke Zhang; Qichen Yuan (Food Chemistry, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Short-range and long-range charge transfer based narrowband deep blue organic fluorescence emitters with EQE > 20% and CIEy ≈ 0.04 - Wenyan Zhao; Zijian Chen; Jihua Tan; Zhenyue Duan; Danhong Zhou; Yanping Huo; Jiuyan Li; Ruifang Wang; Pengzhong Chen; Xiaojun Peng (Chemical Engineering Journal, 2026)

Valorizing jackfruit shell into a hydrothermal liquid seed-priming agent for salinity-stressed crops - Tao Zhang; Yanping Zhu; Yongle Yu; Keyi Zhang; Pan Zhao; Xiaomeng Han; Weigang Wang; Shihu Shu; Dandan Ke; Xiuping Zhan; Xiaoshuang Han; Jiping Shi; et al. (Bioresource Technology Reports, 2026)

Molecular dynamics evidence for bidirectional feedback between PFAS and humic acid during composting: Interaction mechanisms, conformational reorganization, and diffusion regulation - Shujie Hou; Chaoyue Zhao; Xu Li; Yanping Zhang; Bingzhen Li; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Xiaolong Gao; Feng Ma; Yaonan Zhu; Fuxin Yang; et al. (Journal of Hazardous Materials, 2026)

Early thermal pulses drive interfacial pre-aging and plastisphere pre-shaping: An overlooked pre-conditioning pathway in PLA microplastic aging during composting - Yanping Zhang; Youzhao Wang; Chaoyue Zhao; Fuxin Yang; Xu Li; Shujie Hou; Bingzhen Li; Zhengnan Zhu; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Journal of Hazardous Materials, 2026)

Fabrication of RuCo bimetallic catalyst enabling efficient hydrogen generation via ammonia borane hydrolysis - Xianyun Liu; Lu Zhao; Han Wu; Linyan Bian; Yanping Fan; Baozhong Liu (Fuel, 2026)

Phage therapy: A novel strategy to combat drug-resistant Salmonella Pullorum infection in chickens - Hongzhe Zhao; Shilong You; Jiahao Fu; Xiaoyu Xiong; Yingying Ma; Xiaona Wang; Rongyan Li; Fei Teng; Mingze Chen; Wei Wu; Guiwei Li; Yanping Jiang; et al. (Veterinary Microbiology, 2026)

RAD23A promotes multiple myeloma cell survival through DNA damage response, proteostasis and enhanced metabolic activity - Hongxiu Liu; Yihua Wang; Xunru Liu; Ni Yang; Senxin Wang; Jie Zhao; Yaqi Shi; Huichao Wang; Yanping Ma (Toxicology and Applied Pharmacology, 2026)

Corrigendum to “Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting” [J Hazard Mater 503 (2026) 141080] - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Molecular mechanism by which high temperature and RecBCD synergistically lower strand-separation barriers and promote destabilization of representative efflux-pump ARG fragments (macB/tetA) during hyperthermophilic composting - Xu Li; Youzhao Wang; Xiaoyan Dang; Yanping Zhang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Nitrogen doping engineering of Ru nanoparticles/Mo2C MXene for efficient hydrogen production via NH3BH3 hydrolysis - Zhenluo Yuan; Fei Ya; Yang Shi; Shuyan Guan; Pingping Wang; Pei Liu; Shiqian Zhao; Qiuming Peng; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2026)

Uncovering time-lagged causal mechanisms in hyperthermophilic composting using Peter–Clark momentary conditional independence algorithm - Yanping Zhang; Youzhao Wang; Ling Zhou; Fuxin Yang; Xu Li; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Bioresource Technology, 2026)

Assessment of Heavy Metal Pollution in Cultivated Soils and Rice Grains on the South Bank of Taihu Lake, China - Yanping Shi; Yiping Chen; Jiajia Ren; Juntao Zhao; Dan Liu (Bulletin of Environmental Contamination and Toxicology, 2026)

Distribution and potential provenance of metal nanoparticles in sediment core from Daya Bay, northeastern South China Sea - Yumei Song; Dingcheng Wang; Qiaoli Zhong; Shengda Wu; Yanping Zhao; Shuchai Gan; Yulei Xie; Puoengran Guo (Journal of Hazardous Materials, 2026)

E3 ubiquitin ligases in plant defense: mechanisms and prospects for resistance breeding - Yuansheng Wu; Zhengbao Tao; Zheng Qin; Yanping Li; Minkai Zhao; Shanshan Zhao; Jianguo Wu (Science China Life Sciences, 2026)

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Therapeutic potential of Lactobacillus kefiranofaciens ZW18 postbiotic in alleviating hepatocellular carcinoma - Hanxue Xu; Weitao Geng; Jiangye He; Longgang Jia; Gang Zhao; Yanping Wang (Food Research International, 2026)

Comprehensive analysis of lactones and furanones in baijiu: Identification, quantitation, sensorial contribution and aging-related insights - Hao Huang; Yi Li; Huijing Lan; Jia Zheng; Dong Zhao; Jian Su; Yanping Lu; Shuang Chen; Yan Xu (Food Research International, 2026)

Scalable epoxy-based radiative cooling coatings with ternary filler synergy for efficiency and low-cost building thermal management - Qingyun Zhao; Nan Zhang; Zhaoli Zhang; Yikai Zeng; Attia Shady; Yanping Yuan (Energy and Buildings, 2026)

Silymarin sensitizes human colorectal cancer cells to 5-ALA–mediated photodynamic therapy by enhancing cytotoxicity and apoptotic signaling in vitro - JingJing Zhao; Ying Liu; YanPing Zhang; Qin Jiang (DARU Journal of Pharmaceutical Sciences, 2026)

Sequential multi-objective maintenance optimization with dynamic importance ranking: A case study of subsea transportation system - Yixin Zhao; Baoping Cai; Yiliu Liu; Yanping Zhang; Shibo Wu; Gan Li (Ocean Engineering, 2026)

Component-specific microbial degradation and humification mechanisms of typical kitchen waste during winter hyperthermophilic composting in northeastern China - Youzhao Wang; Bingzhen Li; Jiacheng Li; Chaoyue Zhao; Xu Li; Yanping Zhang; Shujie Hou; Feng Ma; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Fuxin Yang; et al. (Journal of Environmental Management, 2026)

Photoelectrotrophic denitrification and iron-sulfur-nitrogen cycle enhance nutrient removal in pyrite-amended constructed wetlands - Xiaoxiao Hou; Lingyun Mu; Yingying Liu; Yanping Xiao; Xinshan Song; Xiaoxiang Zhao; Dong An (Journal of Environmental Management, 2026)

Climate-sensitive environmental drivers shaping epipelagic and mesopelagic fauna biodiversity patterns in the Amundsen–Bellingshausen Seas, Southern Ocean - Jiayu Fan; Yang Liu; Yanping Luo; Yuru Li; Mi Duan; Chunlin Liu; Zhenjiang Ye; Jianchao Li; Peng Sun; Chi Zhang; Jun Zhao; Jianfeng He; et al. (Environmental Research, 2026)

Evaluating microphysics scheme impacts on summer precipitation in Northwestern China using a convection permitting WRF model - Ya Huang; Qingyun Duan; Yong Zhao; Lihua Chen; Yanping Li (Atmospheric Research, 2026)

Non-Invasive functional assessment of severity in cerebral arterial stenosis using cerebral flow fraction: A hemodynamic study - Hao Sun; Bao Li; Zijie Wang; Liyuan Zhang; Jun Zhao; Yanping Zhang; Guangfei Li; Jinli Ding; Yanjun Gong; Hwa Liang Leo; Youjun Liu (Medical & Biological Engineering & Computing, 2026)

Structural equation modeling revealed optimized ridge-furrow configuration integrated with straw-soil crust enhancing carbon sequestration and sainfoin yield in semiarid agroecosystems - Abdul Qadeer; Qi Wang; Rizwan Azim; Xiaole Zhao; Wen Ma; Ibrahim Awuku; Fujia Li; Qinglin Liu; Yanping Liu; Bing Liu; Xuchun Li; Muhammad Sanaullah; et al. (Computers and Electronics in Agriculture, 2026)

Local macrophage dynamics–inspired engineering of time-programmed nano-vaccine scaffold for postoperative cancer immunotherapy - Zhenyu Xu; Qian Chen; Mingyu Hao; Yiyang Cao; Xiaoqin Kuang; Chunjiayu Li; Zhihao Liu; Jiawen Xue; Jianing Zhao; Mengwei Zhao; Naicong Cai; Yiqing Li; et al. (Science Bulletin, 2026)

Phloretin enhances the efficiency of sheep oocyte IVM and early embryonic development by bolstering antioxidant defenses, inhibiting apoptosis, and promoting development - Xu Li; Shuhong Tang; Yinwei Zheng; Ruiguo Zhao; Feifan Xu; Naerhulan Ayiken; Guangdong Hu; Yanping Wang; Weibin Zeng (Reproductive Biology, 2026)

Identification and validating native biocontrol bacteria Bacillus strain MZ3-12 against bacterial wilt - Xiao Zhou; Yue Qing; Yanping Wang; Haibin Deng; Jun Wang; Mi Kuang; Xuefeng Luo; Chenran Zhao; Zheng Sun; Ye Wang; Liang Yang; Wei Ding (Pesticide Biochemistry and Physiology, 2026)

The insecticidal activity and mechanism of the Cinnamomi ramulus (Lauraceae) essential oil against Tribolium confusum Jaquelin Du Val, 1868 (Coleoptera: Tenebrionidae): insights from transcriptomic and metabolomic profiles - Qianqian Lian; Jianji Zhao; Yiqing Li; Hui Tang; Yanping He; Qiuling Tang; Wei Zhang; Jie Bi (Journal of Stored Products Research, 2026)

Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Hour-level humification of papermaking waste residue to produce honeycomb-like controlled-release fertilizer - Dongqing Cai; Shuang Wang; Linying Wang; Zerong Song; Yanping Zhu; Ziyu You; Jinjing Xu; Yan Wang; Wanji Zhu; Rongjun Zhang; Pan Zhao; Xiaofeng Lu; et al. (Journal of Cleaner Production, 2026)

Spatially stratified humification mechanisms in industrial-scale negative-pressure aerated thermophilic composting: Dominant pathways driven by temperature gradients and microbial succession - Shujie Hou; Youzhao Wang; Xu Li; Yanping Zhang; Xiaolong Gao; Jiedong Hao; Bingzhen Li; Ziwei Dai; Feng Ma; Fuxin Yang; Chaoyue Zhao; Tong Zhu (Journal of Environmental Chemical Engineering, 2026)

Preparation of sawdust-based degradable mulch film and nutrient slow-release performance evaluation - Xianghai Kong; Rongxi Hu; Zerong Song; Xinxin Zhai; Ziyu You; Yuhao Wang; Pan Zhao; Xiaofeng Lu; Rongjun Zhang; Yanping Zhu; Dongfang Wang; Dongqing Cai (Journal of Environmental Chemical Engineering, 2026)

Long-distance lateral migration, accumulation and dissipation of natural gas in the northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Faqi He; Wei Zhang; Yanping Ma; Lihua Yang; Deyong Shao; Nan Du; Fuyu Chen (Gondwana Research, 2026)

Solar-driven degradation of HEDP and simultaneous phosphorus recovery from electroplating wastewater via a Cu (III)-mediated biochar electro-Fenton system - Shibo Zhao; Yanping Cui; Qiao Huang; Xian Xiang; Yuqing Qu; Chu Xiong; Bolin Li; Caixia Wen (Chemical Engineering Journal, 2026)

High-resolution skin-like microlithographic displays for visual-tactile system - Baoying Sun; Xiaoli Zhao; Chuang Xue; Mingxin Zhang; Pengbo Xi; Guoqiang Ren; Hao Liu; Junru Zhang; Yanping Ni; Yanhong Tong; Liangwen Feng; Qingxin Tang; et al. (Chemical Engineering Journal, 2026)

Synthesis and biological evaluation of coumarin-based urea derivatives demonstrating apoptosis-inducing and anti-angiogenic properties for non-small cell lung cancer treatment - Zirui Chen; Qi Liao; Pengyu Zhao; Yuefei Geng; Jianguo Wen; Shu Liu; Yanping Tang; Chenjuan Zeng; Tingting Yan; Yongmei Shen; Funeng Geng (Medicinal Chemistry Research, 2026)

Comammox Nitrospira dominates autotrophic nitrification in paddy fields under long-term fertilization - Bingjie Ren; Yanping Wang; Yuchao Wang; Yuling Yang; Zhenfa Su; Haikun Wu; Wangting Yang; Yuhan Jin; Jinghao Jin; Shuai Liu; Lidong Shen; Xu Zhao (Agriculture, Ecosystems & Environment, 2026)

Breaking the cycle of resistance: Hyperthermophilic composting establishes a multi-layered defense against ARG dissemination - Xu Li; Yanping Zhang; Chaoyue Zhao; Xiaoyan Dang; Bingzhen Li; Shujie Hou; Xiaolong Gao; Jiedong Hao; Zhenning Lyu; Youzhao Wang; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

CoOOH-based colorimetric aptasensor with dual cascade amplification for ultrasensitive monitoring of fleroxacin in honey - Yanping He; Peixuan Li; Xin Zhao; Dongmei Wang; Fuqiang Zhang (Food Control, 2026)

One-step microwave fabrication of waste potato-derived bifunctional film: sustainable mulch-fertilizer for plastic substitution - Dongqing Cai; Weijia Liu; Dongfang Wang; Shihu Shu; Pan Zhao; Tao Zhang; Yi Qiao; Xiaoshuang Han; Weijian Zhang; Kaimin Zhu; Rongjun Zhang; Yanping Zhu (Environmental Research, 2026)

Quantifying heavy metal(loid)s sources in subtropical soils and assessing key determinants of their bioavailability: insights from the Yangtze River Delta, China - Minqi Shi; Cheng Wang; Jianhua Wang; Cong Zhong; Yanping Zhao (Plant and Soil, 2026)

Targeting Phospholipid Metabolism as an Effective Hearing Protection Strategy - Huanyu Mao; Wenli Ni; Lupeng Ma; Xiang Li; Yanping Zhang; Yuzheng Zhao; Wenyan Li; Huawei Li; Yan Chen (Neuroscience Bulletin, 2026)

Split biosensor based on nano-enzymatic ferrocene-tyramine deposition reaction for detection of SMP30 antibody - Yanping Xing; Xixiang Xie; Jiangtao Liu; Tao Zhao; Xiyu Liu; Pan Wu; Faquan Lin; Yong Huang (Analytica Chimica Acta, 2026)

Numerical investigations on drag reduction by micro-bubbles of KVLCC2 ship model by means of OpenFOAM - Xiaojie Zhao; Yanping Hao; Jie Cui; Yichen Jiang (Ocean Engineering, 2025)

Chronological and geochemical constraints on the origin and timing of carbonate-cemented sandstones in the Middle Jurassic Zhiluo Formation, northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Yanping Ma; Lihua Yang; Nan Du (Marine and Petroleum Geology, 2025)

Stage-specific bacterial-fungal synergy in industrial-scale hyperthermophilic composting: Community assembly dynamics and modular networks drive humification - Chaoyue Zhao; Youzhao Wang; Feng Ma; Xu Li; Yanping Zhang; Shujie Hou; Bingzhen Li; Xiaodan Zhang; Fuxin Yang; Liying Hao; Tong Zhu (Journal of Environmental Management, 2025)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Ammonium-activated peracetic acid for enhanced tetracycline degradation: Performance and mechanism - Qiao Huang; Yanping Cui; Bolin Li; Chu Xiong; Xian Xiang; Yuqing Qu; Shibo Zhao; Caixia Wen (Environmental Research, 2025)

Fabrication of a nonwoven fabric-based multifunctional mulch film with Cr(VI) remediation capacity - Dongqing Cai; Jinjing Xu; Jiangshan Li; Xianghai Kong; Maowei Wu; Yan Wang; Wanji Zhu; Pan Zhao; Xiaofeng Lu; Xiaoli Tang; Yanping Zhu; Dongfang Wang (Chemical Engineering Journal, 2025)

Genome-wide identification and expression pattern analysis of the dehydrin gene family in Eriobotrya japonica - Yanping Zhang; Xudong Zhu; Shuang Zhao; Mengqing Ge; Pengkai Wang; Tariq Pervaiz; Weizhong You (Horticulture, Environment, and Biotechnology, 2025)

Complete genome sequence and molecular characterization of a novel potyvirus (sweet potato virus H) infecting sweet potato - Wei Tang; Jukui Ma; Yanping Tian; Xiao Yin; Jingwei Chen; Dongjing Yang; Fangyuan Gao; Zhao Liang; Cong Tong; Chengling Zhang; Houjun Sun (Archives of Virology, 2025)

Numerical Analysis of Air-Injection Drag Reduction for the KVLCC2 Hull Using the VOF Interface-Capturing Method - Xiaojie Zhao; Yanping Hao; Qi Zhang (Journal of Marine Science and Engineering, 2025)
To investigate the air layer drag reduction and the related flow field characteristics of ships, the gas–liquid two-phase numerical model using the VOF solver in STAR-CCM+ has been established, considering the effects of free surface and surface tension. The numerical model is first validated through experimental results for the drag reduction by air-injection on a simplified ship model. Then, the numerical simulations for the KVLCC2 at varying speeds and air-injection rates are conducted, considering different ship attitudes and air-injection surface configurations. The impacts of flow velocity, air-injection rates, ship attitude and air-injection configurations on air layer drag reduction are analyzed. The distributions of air and pressure around the ship and their influence mechanisms on drag reduction are discussed. The simulation results show that the drag reduction exhibits a positive correlation with air-injection rate until it reaches an optimal peak value. The combined action of the incoming flow and injection velocities causes the vortex recirculation of the air layer under the ship, leading to its disruption and the subsequent formation of air-free zones on the hull bottom. High air-injection rates and the stern trim induce air layer lateral spillage, increasing frictional resistance on the hull side surfaces. An air layer on the stern surface will reduce the viscous pressure resistance by changing the flow separation near the ship stern. Air-layer coverage area is closely correlated with inflow velocity and injection surface configurations. The reasonable configurations of the air-injection surfaces can significantly improve the drag reduction.

Adapting to hypo-salinity: Molecular mechanisms in giant clams and symbionts with implications for coral reef resilience under climate change - Zhen Zhao; Xixi Duan; Tao Zhang; Siqi Bi; Zohaib Noor; Shuming Guo; Zonglu Wei; Yinjie Zhang; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; et al. (Environmental Research, 2025)

Reaction route innovates design of metal supported single atom electrocatalysts for hydrogen evolution: A review - Zeyu Zhao; Ting Chen; Bing Ding; Shengliang Zhang; Duo Chen; Gao Chen; Yanping Zhu; Xiaogang Zhang (Chemical Engineering Journal, 2025)

Suitable ridge width and straw length for alfalfa production under ridge-furrow rainwater harvesting compacted with chopped straw-soil crust in semiarid regions - Rizwan Azim; Qi Wang; Xuchun Li; Abdul Qadeer; Xiaole Zhao; Ibrahim Awuku; Wen Ma; Qinglin Liu; Yanping Liu; Bing Liu (Plant and Soil, 2025)

The latest advances on the formation, exposure level and control strategies of nitrosamines in meat, poultry and fish products - Minting Guo; Yanping Xian; Xiaojuan Zhao; Min Qian; Jun Li; Xiaofang Zeng; Weidong Bai; Hao Dong (Food Chemistry, 2025)

Effects of inorganic salt ions on long-term retrogradation characteristics of lotus seed starch under microwave treatment - Yingting Zhao; Zhiyang Lu; Yang Liu; Yanping Lei; Yuting Tian (Food Hydrocolloids, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Ultrasound-triggered piezocatalytic MOF(Hf)-Pt nanozymes for efficient ROS scavenging in the treatment of osteoarthritis - Yi Yao; Zixin Gao; Zhongjie Pan; Yanping Zhong; Lili Qin; Kexin Zhao; Shuhan Liu; Shengqing Zhang; Haoyang Han; Feiying Yin; Ruizheng Liang; Jinmin Zhao; et al. (Chemical Engineering Journal, 2025)

High entropy relaxation ferroelectric ceramics with strong coupled achieved by framework structure guided design and grain boundary optimisation - Renkai Zhao; Kaijie Chen; Wenhua Li; Xingui Tang; Zhifei Jian; YongXi Liang; Jiayi Yin; Yanping Jiang; Xiaobin Guo; Kai Yan (Chemical Engineering Journal, 2025)

Exploring the symbiotic resilience of boring giant clams and zooxanthellae during heatwave conditions: An investigation into strategic countermeasures - Zhen Zhao; Siqi Bi; Liqiang Zhao; Zohaib Noor; Shuming Guo; Zonglu Wei; Xixi Duan; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; Kotaro Shirai; et al. (Aquaculture, 2025)

Electron beam/persulfate-induced second-scale upcycling of wastewater polyvinyl alcohol with ultra-low chemical input - Tao Zhang; Yanping Zhu; Yongle Yu; Xiaoya Pan; Pan Zhao; Shihu Shu; Dongfang Wang; Jiping Shi; Li Liu; Weijian Zhang; Bin Huang; Xiaofeng Lu; et al. (Water Research, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Functional integrated in gel polymer electrolytes: A handy approach for achieving superior wide temperature range operation sodium metal batteries - Yubin Liao; Fangkun Li; Yadong Zhou; Xijun Xu; Hangyu Zhang; Weizhen Fan; Yanxue Wu; Jingwei Zhao; Jun Liu; Yanping Huo (Chemical Engineering Journal, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Performance of an integrated modeling framework for spring wheat yield simulation in Saskatchewan, Canada - Qi Zhao; Fei Huo; Yanping Li; Zhenhua Li; Lina Wu (Agricultural and Forest Meteorology, 2025)

Corrosion characteristics of low-carbon cast steel ZG230-450 in chloride-sulfate atmospheric environment - Xuan Zheng; Yanping Zhao; Hongxin Yang; Baorong Liu; Chi Zhang (Environmental Science and Pollution Research, 2025)

Enhanced extraction of microplastics from terrestrial animal intestinal tissues via optimized fenton oxidation - Simin Yu; Jiaqi Chen; Zhanao Zhang; Yanping Zhao; Yan Zhang (Journal of Hazardous Materials, 2025)

Enhancing manganese redox-driven nitrogen removal by integrating manganese ore with microelectrolysis into constructed wetlands - Xiaoxiao Hou; Wei Huang; Xinshan Song; Yingying Liu; Yanping Xiao; Xiaoxiang Zhao; Dong An (Bioresource Technology, 2025)

OCCMNet: Occlusion-Aware Class Characteristic Mining Network for multi-class artifacts detection in endoscopy - Chenchu Xu; Yu Chen; Jie Liu; Boyan Wang; Yanping Zhang; Jie Chen; Shu Zhao (Medical & Biological Engineering & Computing, 2025)

Persistent Wnt signaling affects IVF embryo implantation and offspring metabolism - Yanping Jia; Yingdong Liu; Yanhe Li; Xiaohong Guan; Junting Xu; Zihui Yan; Kuisheng Liu; Yalin Zhang; Dandan Bai; Jiani Xiang; Yan Zhang; Shangyu Hou; et al. (Science Bulletin, 2025)

Hydrothermal reduction and phase transformation of Fe(III) minerals induced by rice straw to improve the heterogeneous Fenton degradation of metolachlor - Jingyi Liu; Yu Zhao; Liulong Cheng; Zhuoye Lu; Haojie Liang; Runliang Zhu; Yue Wang; Fangxin Deng; Zhuobiao Ni; Yaying Li; Guangwei Yu; Jing Zhang; et al. (Journal of Hazardous Materials, 2025)

The independent and joint effects of meteorological factors on influenza: A nationwide time series study in China - Mengen Guo; Yunfei Zhang; Jianxiong Hu; Aga Zheng; Guanhao He; Xiaokun Yang; Hongting Zhao; Tao Liu; Fengrui Jing; Ziqiang Lin; Yanping Zhang; Maigen Zhou; et al. (Urban Climate, 2025)

Zwitterionic-based hybrid monoliths for capillary microextraction of polypeptides in dairy products - Xiaoyun Lei; Yaping Jiang; Yang Li; Yanping Duan; Ting Guo; Tianlei Zhang; Zuoping Zhao; Huiping Dai; Xiaohui Ji (Food Chemistry, 2025)

A gut bacterial supplement for Asian honey bee (Apis cerana) enhances host tolerance to nitenpyram: Insight from microbiota–gut–brain axis - Chonghui Zhao; Yehua Peng; Muhammad Fahad Raza; Wenbo Wang; Yi Zhang; Yanping Chen; Richou Han; Jun Guo; Shaokang Huang; Wenfeng Li (Environmental Research, 2025)

Translocation coefficients of heavy metals in the soil-rice system and their environmental implication - Cheng Wang; Minqi Shi; Jianhua Wang; Cong Zhong; Yanping Zhao (Plant and Soil, 2025)

Comparison of genetic diversity and population structure of Saccostrea mordax lineages A, B, and C across South China Sea and Celebes Sea - Yinjie Zhang; Haitao Ma; Chenghui Han; Zhen Zhao; Zonglu Wei; Xixi Duan; Jiangwei Li; Yanping Qin; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Frontiers in Marine Science, 2025)
Saccostrea mordax is an ecologically important bivalve species and a potential genetic resource for oyster breeding that inhabit in the Indo-Western Pacific region, characterized by three distinct lineages: A, B, and C. However, limited information is available about its genetic variation and genetic structure. The present study was conducted to study genetic diversity and population structure of S. mordax lineages A, B, and C based on mitochondrial COI gene data across the South China Sea and Celebes Sea. The UPGMA phylogenetic tree among populations, BI phylogenetic tree among individuals and median network revealed three main clusters, corresponding to S. mordax lineages A, B, and C. The results of K2P sequence divergence, pairwise Φ st, gene flow and AMOVA indicated clear genetic differences among the lineages, combined with sympatric in all 7 geographical populations, these suggests lineages A and B are transitional periods of new species formation. Moreover, different patterns of population subdivision were found within lineages A, B and C. In lineage A, significant genetic differentiation was only observed between YM (Celebes Sea) and other populations (South China Sea), with a significant correlation between geographical distance and genetic distance among populations. In lineages B and C, there was no genetic differentiation between YM (Celebes Sea) and other populations (South China Sea), and no significant correlation between genetic distance and geographical distance among populations. The population history analyses indicated that populations of lineage A have experienced a recent sudden expansion, while populations of lineages B and C were large stable. These findings are essential for the conservation, sustainable utilization, and ecological restoration of S. mordax .

Global prevalence of Porcine Astrovirus: A systematic review and meta-analysis - Xiaoyu Ge; Yize Li; Feipeng Zhao; Xin’ao Ma; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2025)

2,4,6-trinitrotoluene induces neurotoxicity by affecting the G protein pathways in Caenorhabditis elegans - Ying Li; Yanping Zhou; Chunyan Wang; Yaguang Nie; Yongbing Zhu; Sanping Zhao; Lijun Wu; An Xu (NeuroToxicology, 2025)

Multi-objective decision-making considering future demands helps to delineate key areas for ecological restoration in Changsha-Zhuzhou-Xiangtan urban agglomeration, China - Tao Li; Sheng Li; Yanping Zhao; Hua Zheng; Kuan Wang; Mi Yi (Journal of Environmental Management, 2025)

Paracoccus yibinensis sp. nov., a novel bacterium with astaxanthin producing isolated from the environment of Chinese distilled Baijiu - Qingchun Luo; Yanping Lu; Xi Li; Jian Su; Pengju Zhao; Zhu Zhang; Yang Gu; Dong Zhao; Jia Zheng (Antonie van Leeuwenhoek, 2025)

Influencing Factors on Oyster Recruitment and Performance Evaluation for Oyster Reef Restoration in Tianjin Coastal Zones - Yuxuan Zhao; Chen Yang; Bo Zhang; Yanping Li; Jianbo Tu; Fuxin Niu; Wenliang Kong; Zhiyun Wang; Xianhua Liu (Oceans, 2025)
Global oyster reefs have suffered severe degradation due to human activities, environmental pollution, and climate change. The construction of artificial reefs offers a promising strategy to enhance oyster recruitment and mitigate population decline. However, the factors influencing oyster recruitment in artificial frameworks remain largely unclear, and it is still challenging to evaluate the effectiveness of different restoration methods. In this study, a series of oyster reef restoration experiments were conducted in the Tianjin coastal zone to identify key factors affecting recruitment success. These factors included restoration methods (shell string, mesh bag, and mesh cage), seeding with juvenile oysters, oyster shell orientation, and cultch hanging height. Our results indicated that the mesh bag method achieved the highest oyster settlement density in the intertidal zone, while the shell string method supported the fastest growth rates of oysters in the subtidal zone. The lower hanging height of cultches in the artificial frames increased oyster settlement density; however, hanging the cultches too close to the sediment negatively impacted oyster growth rates. Additionally, seeding with juvenile oysters and orienting the rough side of the shell upward enhanced recruitment performance. Oyster settlement density was greater in the intertidal zone (Bagua Shoal) compared to the subtidal zone (Dashentang), while oysters in the subtidal zone exhibited faster growth rates. Using redundancy analysis, the influence of environmental factors on the oyster recruitment performance was assessed. Oyster growth in the subtidal zone was positively correlated with dissolved oxygen and pH, whereas oyster settlement density in the intertidal zone was positively associated with water temperature, chlorophyll a concentration, and salinity. Finally, we evaluated the effectiveness of different restoration methods by considering factors including reef construction costs, oyster settlement abundance, average daily shell growth rate, water purification potential, and reef subsidence. Our results demonstrated that the shell string method was the most effective in the Dashentang subtidal zone, while the mesh bag method with oyster seeding was optimal in the Bagua Shoal intertidal zone. Our findings can provide valuable insights and guidance for oyster reef restoration projects.

Chinese chestnut did not induce negative plant soil feedback during centuries of growth - Xu Cheng; Zhichun Yan; Qian Li; Lucas Schmitz; Jundi Yan; Yueyang Ge; Yanping Lan; Yaceng Zhao; Yiyang Wang; Guangdong Li; Yang Liu; Martinus Schneijderberg; et al. (Science of The Total Environment, 2025)

Enhancing humification in high-temperature composting: Insights from endogenous and exogenous heating strategies - Chaoyue Zhao; Feng Ma; Youzhao Wang; Xu Li; Yanping Zhang; Zhipeng Wang; Wei Xiong; Xiaolong Gao; Yongguang Ma; Fuxin Yang; Tong Zhu (Bioresource Technology, 2025)

Genetic diversity and genetic structure in successive mass selected generations of tetraploid Pacific oysters (Crassostrea gigas), diploid Portuguese oysters (C. angulata) and their allotriploid oysters - Haitao Ma; Yanping Qin; Yinjie Zhang; Weitao Wan; Jingyue Huang; Na Mi; Zhen Zhao; Zhongyu Wang; Jiangwei Li; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2025)

Occurrence and ecological risk of disinfection byproducts in urban water body during the pandemic in the Pearl River Delta - Huazhi Wu; Lin Zhang; Pengran Guo; Yanping Zhao; Yumei Song; Xuerong Zhang; Yongqian Lei; Jingwei Xu (Journal of Hazardous Materials, 2025)

Forest transformation increases soil N2O fluxes in an unmanaged Moso bamboo forest - Yibo Yan; Xueying Tu; Hui Zhang; Yang Lv; Yihui Zhao; Ao Hu; Yanping Wu; Caixian Tang; Yixiang Wang (Forest Ecology and Management, 2025)

Engineered ADSCs and doxycycline encapsulated antibacterial, immunomodulatory and proangiogenic hydrogels for infected burn wound healing - Yanan Gu; Zhen Liang; Yanping Wang; Zhou Yu; Yubo Shi; Jinlong Luo; Xianghao Xu; Ke Fang; Hanli Wang; Baolin Guo; Baoqiang Song; Xin Zhao (Chemical Engineering Journal, 2025)

Anti-inflammatory, anti-colitis, and antioxidant effects of columbianadin against DSS-induced ulcerative colitis in rats via alteration of HO-1/Nrf2 and TLR4-NF-κB signaling pathway - Yanping Zhang; Ping Cao; Dongyuan Qin; Ying Zhao; Xing Chen; Peng Ma (Inflammopharmacology, 2025)

Effects of cloprostenol and oxytocin on ultrasonographic changes of uterine horns in postpartum primiparous Hu sheep - Yixuan Li; Zongling Liu; Wenqian Zhang; Chunhao Zhu; Xi Chen; Yukun Zhao; Lei Liu; Ting Ting Zhu; Mingyang Geng; Yanping Wang; Weibin Zeng (Animal Reproduction Science, 2025)

Analysis of molecular identity and function of putative serotonin receptors in the Giant clam (Tridacna crocea) and the potential role of 5-HT1D-like receptor in reproduction - Xiaogang Yang; Zohaib Noor; Shuming Guo; Zhen Zhao; Borui Cai; Guozhao Huang; Haitao Ma; Yanping Qin; Ziniu Yu; Jun Li; Yuehuan Zhang (Aquaculture, 2024)

Assessing the feasibility of adjusting the dry matter content utilizing corn grits and cottonseed meal and inoculating with Lactiplantibacillus plantarum in the production of fermented feed from kitchen waste - Yupeng Tang; Fengyuan Yang; Huili Pang; Shanshan Zhao; Hengyu Ma; Haolong Li; Yuhang Huang; Pintian Sun; Xiaoxue Tang; Yanping Wang (Process Safety and Environmental Protection, 2024)

Ferrihydrite optimizing Feammox inoculum to enhance ammonia removal from concentrate wastewater through continuous upflow anaerobic sludge blanket (UASB) - Linji Xu; Lin Li; Jianxi Liu; Xingzu Wang; Yanping Zhao; Jujiao Zhao; Li Gu; Qiang He; Xinzhu Wang; Jinhua Zhang (Journal of Environmental Chemical Engineering, 2024)

Antimicrobial activities of natural flavonoids against foodborne pathogens and their application in food industry - Yanping Wu; Ling Jiang; Wenyi Ran; Kai Zhong; Yinglan Zhao; Hong Gao (Food Chemistry, 2024)

Mobilization of phosphorus in sediments of eutrophic lakes induced by elevated sulfate levels - Lanqing Zhang; Miaotong Yu; Simin Yu; Huaizhi Chen; Mengmeng Xiao; Guoxiang Wang; Yanping Zhao (Science of The Total Environment, 2024)

Can combined wind and solar power meet the increased electricity load on heatwave days in China after the carbon emission peak? A case study in southern Hebei - Jie Bai; Mingxin Zhao; Xiaohui Qin; Yanping Xu; Yang Liu (Journal of Cleaner Production, 2024)

Characterization and prediction of demand response potential of air conditioning systems integrated with chilled water storage - Wanfang Zhao; Jinqing Peng; Jingyu Cao; Rongxin Yin; Jiaming Song; Yanping Yuan (Energy and Buildings, 2024)

ChCaspase-1 cleaves ChGasdermin-E, inducing pyroptosis, and participates in the bacterial defence of the oyster Crassostrea hongkongensis - Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Ruwen Yang; Shu Xiao; Fan Mao; Yanping Qin; Haitao Ma; Yuehuan Zhang; Yang Zhang; ZiniuYu; et al. (Aquaculture, 2024)

PhERF71 regulates petunia flower senescence by modulating ethylene biosynthesis - Xiaotong Ji; Yanxiang Mao; Yanping Yuan; Meiling Wang; Yike Zhao; Lei Zhang; Daoyang Sun (Postharvest Biology and Technology, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

Adsorption mechanism and remediation of heavy metals from soil amended with hyperthermophilic composting products: Exploration of waste utilization - Feng Ma; Tong Zhu; Youzhao Wang; Shuichi Torii; Zhipeng Wang; Chaoyue Zhao; Xu Li; Yanping Zhang; Haoyu Quan; Chunli Yuan; Liying Hao (Bioresource Technology, 2024)

Cellular Senescence-Related Long Non-coding RNA Signatures Predict Prognosis in Juvenile Osteosarcoma - Peng Zhao; Junli Chang; YeKai Chen; Xingyuan Sun; Xiaoping Ma; Chujie Zhou; Lei Zhou; Yongjun Wang; Yanping Yang (Phenomics, 2024)
Osteosarcoma is the most common malignant bone tumor and is frequently diagnosed in juvenile. Cellular senescence is a fundamental hallmark of osteosarcoma and plays a vital role in the initiation and progression of aging and tumorigenesis. Long non-coding RNAs (lncRNAs) are implicated in tumorigenesis. In this study, six cellular senescence-related lncRNAs with independent prognostic significance in juvenile osteosarcoma patients were identified through univariate Cox regression analysis, least absolute shrinkage and selection operator (LASSO) regression analysis, and multivariate Cox regression analysis. Prognostic significance was further confirmed by Kaplan–Meier (KM) survival curves, co-expression interaction networks, and sankey diagrams. A prognostic model of cellular senescence-related genes in juvenile osteosarcoma patients was then constructed using multivariate Cox regression analysis based on these six genes. High- and low-risk groups were identified according to the median risk score calculated by the prognostic model. The favorable prognostic significance of this model was demonstrated through survival curves, receiver operating characteristic (ROC) curves, distribution scatter plots and lncRNA expression heatmaps. Furthermore, cellular senescence-related lncRNAs were validated by enrichment analysis, immunological correlation analysis, m 6 A correlation analysis, and drug sensitivity correlation analysis. These findings are important for improving the prognosis of juvenile osteosarcoma patients and understanding the mechanisms underlying cellular senescence in juvenile osteosarcoma development.

Design of Auto-Adaptive Drug Delivery System for Effective Delivery of Peptide Drugs to Overcoming Mucus and Epithelial Barriers - Ruihuan Ding; Yanping Li; Wei Zheng; Yiying Sun; Zhenyu Zhao; Houqian Zhang; Ranran Yuan; Aiping Wang; Kaoxiang Sun; Hongbo Wang; Yanan Shi (The AAPS Journal, 2024)

Effective strategy for Cr(VI) removal from water in evolution process of ferroan brucite by redox and intercalation - Shifeng Zhao; Fengzhu Lv; Yanping Zhao; Jiajing Feng; Hanxia Tang (Journal of Water Process Engineering, 2024)

High recoverable energy storage density and efficiency achieved in doped NaNbO3 ceramics via composition design strategy for pulsed power capacitor - Renkai Zhao; Kaiyuan Wang; Wenhua Li; Yujia Yuan; Xingui Tang; Jia Hu; HuaXiang Fan; Kaijie Chen; Wanglai Song; Yanping Jiang; Xiaobing Guo (Chemical Engineering Journal, 2024)

Condition-based maintenance method for multi-component systems under discrete-state condition: Subsea production system as a case - Rongkang Li; Baoping Cai; Yixin Zhao; Yiliu Liu; Yanping Zhang; Xiangdi Kong; Yonghong Liu (Ocean Engineering, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

An EEG-based marker of functional connectivity: detection of major depressive disorder - Ling Li; Xianshuo Wang; Jiahui Li; Yanping Zhao (Cognitive Neurodynamics, 2024)

Community Structure Characteristics and Changes in Fish Species at Poyang Lake after the Yangtze River Fishing Ban - Yanping Zhang; Haixin Zhang; Zijun Wu; Mingguang Zhao; Guangpeng Feng (Fishes, 2024)
To understand the fish community structure characteristics and changes in Poyang Lake after the Yangtze River fishing ban in 2021, seven sampling stations were established, namely in Hukou, Lushan, Duchang, Yongxiu, Nanjishan, Ruihong, and Poyang, for fishery resource surveys between 2020 and 2021. The results showed that 93 fish species were identified, belonging to 11 orders, 20 families, and 61 genera, which was an increase of 4.5% from before the fishing ban. Of these, 52 Cyprinidae species were identified, comprising the highest proportion (55.91%). Four invasive alien species (hybrid sturgeon, Cirrhina mrigala, Piaractus brachypomus, and Mugil cephalus) were identified, and the number of alien species in Poyang Lake was higher than before the fishing ban. Carnivorous and mid-lower-level fish showed a significant increase, accounting for 47.31% and 38.71% of the total species, respectively. Compared with the Yangtze River before the fishing ban, the body length and body weight of the main economic fish in Poyang Lake increased by 6.10–61.26% and by 15.14–291.57%, respectively. In terms of age structure, the proportion of major economically important fish aged 1 or 2 years decreased significantly, while the proportion of older fish increased substantially. There was little difference in the diversity of fish communities at different stations in Poyang Lake. In terms of biodiversity, the Shannon–Wiener index ranged from 2.158 to 2.909, with Poyang having the highest value and Nanjishan the lowest. Margalef’s index ranged from 4.265 to 6.459, with Lushan having the highest value and Nanjishan the lowest. Pielou’s index ranged from 0.617 to 0.822, with Duchang having the highest value and Nanjishan the lowest. Hence, the Yangtze river fishing ban has played an important and positive role in the restoration of fishery resources in Poyang Lake. However, long-term tracking and monitoring are needed to provide information to comprehensively evaluate the ecological impact of the Poyang Lake fishing ban.

Involvement of a rice mutation in storage protein biogenesis in endosperm and its genomic location - Huaidong Tian; Ying Li; Yanping Guo; Yajuan Qu; Xiaoye Zhang; Xiaoxian Zhao; Xinya Chang; Baohua Tian; Guangyuan Wang; Xiangmei Yuan (Planta, 2024)

The conversion of monolignans to sesquilignans and dilignans is closely correlated to the regulation of Arctium lappa seed germination - Rong Zhao; Ying Yu; Mingze Gao; Yanping Xing; Jianing Xue; Liang Xu; Tingguo Kang (Planta, 2024)

Resistance of an intertidal oyster(Saccostrea mordax)to marine heatwaves and the implication for reef building - Shuming Guo; Jun Li; Xiaogang Yang; Yanping Qin; Yuexin Zhao; Jinkuan Wei; Haitao Ma; Ziniu Yu; Liqiang Zhao; Yuehuan Zhang (Science of The Total Environment, 2024)

Recent advances in the authentication (geographical origins, varieties and aging time) of tangerine peel (Citri reticulatae pericarpium): A review - Yanxin Li; Wenhong Zhao; Min Qian; Zhiyi Wen; Weidong Bai; Xiaofang Zeng; Hong Wang; Yanping Xian; Hao Dong (Food Chemistry, 2024)

Multifunctional Ac@ZIF-8/AgNPs nanoplatform with pH-responsive and ROS scavenging antibacterial properties promotes infected wound healing - Yipeng Pang; Maofang Zhao; Yuhan Xie; Yanping Wang; Yuxin You; Yongding Ke; Chaoyi Zhang; Xiaohan Chen; Yijia Yang; Chunlei Zhang; Xi Chen; Yi Liu; et al. (Chemical Engineering Journal, 2024)

TCE degradation of modified graphite felt cathode in a flow-through electro-Fenton system and its H2O2 production ability in a real contaminated field - Yanping Cui; Haodong Yang; Xian Xiang; Shibo Zhao; Qiao Huang; Zhaoqiang Huang (Chemical Engineering Journal, 2024)

Correction to: Changes in the characteristics of soil dissolved organic matter over time since inter-planting with white clover (Trifolium repens L.) in apple orchards on the Loess Plateau in China - Rongqin Zhang; Ming Li; Xiaodong Gao; Yumin Duan; Yaohui Cai; Huike Li; Xining Zhao; Yanping Wang (Plant and Soil, 2024)

Changes in the characteristics of soil dissolved organic matter over time since inter-planting with white clover (Trifolium repens L.) in apple orchards on the Loess Plateau in China - Rongqin Zhang; Ming Li; Xiaodong Gao; Yumin Duan; Yaohui Cai; Huike Li; Xining Zhao; Yanping Wang (Plant and Soil, 2024)

A within-subject voxel-wise constant-block partial least squares correlation method to explore MRI-based brain structure–function relationship - Xiaoyu Zhao; Kewei Chen; Hailing Wang; Yufei Gao; Xiangmin Ji; Yanping Li (Cognitive Neurodynamics, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Ecological risk assessment of the typical anti-epidemic drugs in the Pearl River Delta by tracing their source and residual characteristics - Huazhi Wu; Liying Bin; Pengran Guo; Yanping Zhao; Chao Chen; Zhiliang Chen; Bing Tang (Journal of Hazardous Materials, 2024)

Preparation of smart magnetic fluids and application in sewage treatment: Copper adsorption, kinetic and isotherm study - Deli Xiao; Hui Jiang; Yunlin Zhou; Alhassan Imran; Hongyan Zhao; Yanping Bi (Journal of Environmental Management, 2024)

Identification, characterisation and expression analysis of peanut sugar invertase genes reveal their vital roles in response to abiotic stress - Tingting Mao; Yaru Zhang; Wenwen Xue; Yu Jin; Hongfei Zhao; Yibo Wang; Shengnan Wang; Shengjie Zhuo; Feifei Gao; Yanping Su; Chunyan Yu; Xiaotong Guo; et al. (Plant Cell Reports, 2024)

Molecularly imprinted polymer sheathed mesoporous silica tube as SPME fiber coating for determination of tobacco-specific nitrosamines in water - Yuemei Chen; Yang Yu; Shaohan Wang; Jiajia Han; Mengge Fan; Yanping Zhao; Junlang Qiu; Xin Yang; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Nature reserves and reforestation expend the potential habitats for endangered plants: A model study in Cangshan, China - Yujuan Yan; Canjun Zhao; Yanping Xie; Xianfeng Jiang (Journal for Nature Conservation, 2024)

Understanding quality differences between kiwifruit varieties during softening - Fan Yang; Renkai Zhao; Jiangtao Suo; Yuduan Ding; Jiawei Tan; Qinggang Zhu; Yanping Ma (Food Chemistry, 2024)

Seismic response of a mid-story isolated structure considering SSI in mountainous areas under long-period earthquakes - Feng Wan; Shengwu Qin; Dewen Liu; Tiange Zhao; Yanping Zheng; Hang Shan; Zhiang Li; Fusong Peng; Jingran Xu; Min Lei (Earthquake Engineering and Engineering Vibration, 2024)

Gas-expanded pore MOF derived Sm/MnOx catalysts enable ultralow-temperature selective catalytic reduction of NOx - Shengchen Li; Dan Zhao; Shunli Shi; Fangyu Zhu; Yanping Yang; Shuhua Wang; Shunmin Ding; Chao Chen (Journal of Environmental Chemical Engineering, 2023)

Carcass meat quality, volatile compound profile, and gene expression in Tan sheep under different feeding regimes - Xingang Zhao; Shuxian Zuo; Yanping Guo; Can Zhang; Yuejun Wang; Sijia Peng; Ming Liu; Bing Wang; Hao Zhang; Hailing Luo (Food Bioscience, 2023)

Multi-omics analysis of oxidative stress and apoptosis in hepatopancreas cells induced by Polyascus gregaria parasitizing the Eriocheir sinensis - Shiwei Zhao; Qingbiao Hu; Hongbo Jiang; Yingying Zhao; Yanping Wang; Chengcheng Feng; Xiaodong Li (Fish & Shellfish Immunology, 2023)

Controlled synthesis of CuS with different morphology and pollution control of Hg0 in non-ferrous smelting flue gas - Jin Zhao; Xueqian Wu; Yanping Ma; Wei Liu; Zhen Li; Songjian Zhao (Fuel, 2023)

Divergent temporal changes of heavy metals in the soil induced by natural versus anthropogenic forces: A case study in the Yangtze River delta area, China - Cheng Wang; Jianhua Wang; Cong Zhong; Yanping Zhao (Science of The Total Environment, 2023)

Insight into the plant-associated bacterial interactions: Role for plant arsenic extraction and carbon fixation - Yibo Liu; Baiyu Zhang; Ye Yao; Bo Wang; Yiqi Cao; Yanping Shen; Xiaohui Jia; Fukai Xu; Ziwei Song; Chengpeng Zhao; HongJie Gao; Ping Guo (Science of The Total Environment, 2023)

Superhigh and ultrafast removal of congo red and methylene blue in the evolution process of ferroan brucite with multiple mechanism - Shifeng Zhao; Yanping Zhao; Zhiming Wu; Fengzhu Lv; Guocheng Lv; Libing Liao (Journal of Environmental Chemical Engineering, 2023)

ZIF-8-derived hollow carbon polyhedra with highly accessible single Mn-N6 sites as peroxymonosulfate activators for efficient sulfamethoxazole degradation - Yue Zhao; Rui Gao; He Wang; Yanping Sun; Xiaohui Zhan; Lei Chen; Junyan Liu; Huixiang Shi (Chemical Engineering Journal, 2023)

Biocrust and sand burial together promote annual herb community assembly in an arid sandy desert area - Yanhong Gao; Rongliang Jia; Yanping Liu; Yun Zhao; Yongshen Wu; Haotian Yang; Lichao Liu; Yulong Duan; Lina Zhao; Wanxue You (Plant and Soil, 2023)

Fractionations of heavy metals and their correlations with magnetic susceptibility in soil from a typical alluvial island in the lower yangtze river, China - Cheng Wang; Rong Ma; Jianhua Wang; Cong Zhong; Yanping Zhao; Patrick Browne (Journal of Cleaner Production, 2023)

Development of statistical regression and artificial neural network models for estimating nitrogen, phosphorus, COD, and suspended solid concentrations in eutrophic rivers using UV–Vis spectroscopy - Yanping Lyu; Wenpeng Zhao; Tsuyoshi Kinouchi; Tadahiro Nagano; Shigeo Tanaka (Environmental Monitoring and Assessment, 2023)
River water quality monitoring is crucial for understanding water dynamics and formulating policies to conserve the water environment. In situ ultraviolet–visible (UV–Vis) spectrometry holds great potential for real-time monitoring of multiple water quality parameters. However, establishing a reliable methodology to link absorption spectra to specific water quality parameters remains challenging, particularly for eutrophic rivers under various flow and water quality conditions. To address this, a framework integrating desktop and in situ UV–Vis spectrometers was developed to establish reliable conversion models. The absorption spectra obtained from a desktop spectrometer were utilized to create models for estimating nitrate-nitrogen (NO 3 -N), total nitrogen (TN), chemical oxygen demand (COD), total phosphorus (TP), and suspended solids (SS). We validated these models using the absorption spectra obtained from an in situ spectrometer. Partial least squares regression (PLSR) employing selected wavelengths and principal component regression (PCR) employing all wavelengths demonstrated high accuracy in estimating NO 3 -N and COD, respectively. The artificial neural network (ANN) was proved suitable for predicting TN in stream water with low NH 4 -N concentration using all wavelengths. Due to the dominance of photo-responsive phosphorus species adsorbed onto suspended solids, PLSR and PCR methods utilizing all wavelengths effectively estimated TP and SS, respectively. The determination coefficients ( R 2 ) of all the calibrated models exceeded 0.6, and most of the normalized root mean square errors (NRMSEs) were within 0.4. Our approach shows excellent efficiency and potential in establishing reliable models monitoring nitrogen, phosphorus, COD, and SS simultaneously. This approach eliminates the need for time-consuming and uncertain in situ absorption spectrum measurements during model setup, which may be affected by fluctuating natural and anthropogenic environmental conditions.

A novel high-stability bioelectrochemical sensor based on sol-gel immobilization of lactate dehydrogenase and AuNPs-rGO signal enhancement for serum pyruvate detection - Yanping Zhao; Xu Geng; Xiaoling Zhou; Li Xu; Shuai Li; Zhengqiang Li; Yi Guo; Chen Li (Analytica Chimica Acta, 2023)

Enhanced trichloroethylene biodegradation: The mechanism and influencing factors of combining microorganism and carbon‑iron materials - Jing Ma; Manxi Xie; Nan Zhao; Yue Wang; Qingqi Lin; Yanping Zhu; Yuanqing Chao; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

Molecular cloning, functional characterization and expression of the β-amyrin synthase gene involved in saikosaponin biosynthesis in Bupleurum chinense DC. - Yanping Mao; Hua Chen; Jun Zhao; Yuchan Li; Liang Feng; Yuping Yang; Yiguan Zhang; Ping Wei; Dabin Hou (Journal of Plant Biochemistry and Biotechnology, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Exploration of the metabolic flexibility of glycogen accumulating organisms through metatranscriptome analysis and metabolic characterization - Bin Zhao; Yanping Yang; Chen Zhao; Chunchun Zhang; Zhaohui Zhang; Liang Wang; Shang Wang; Jingfeng Wang (Journal of Environmental Sciences, 2023)

First kinetics verification of the useful H2Ogas inhibition on the thermal regeneration of spent activated carbon in flue gas desulfurization - Hanyu Deng; Wenzhen Cai; Lanhe Zhang; Yanping Jia; Xiaoqiang Wang; Qing Zong; Guishi Cheng; Xiaoying Hu; Changqing Dong; Ying Zhao (Fuel, 2023)

Revisiting the biological pathway for methanogenesis in landfill from metagenomic perspective—A case study of county-level sanitary landfill of domestic waste in North China plain - Qiuling Dang; Xinyu Zhao; Yanping Li; Beidou Xi (Environmental Research, 2023)

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

Calycosin-7-glucoside promotes mitochondria-mediated apoptosis in hepatocellular carcinoma by targeting thioredoxin 1 to regulate oxidative stress - Xiaodong Wei; Yanping Zeng; Fancheng Meng; Tingpu Wang; Hebin Wang; Yijun Yuan; Dongmei Li; Yue Zhao (Chemico-Biological Interactions, 2023)

Inhibition of aged microplastics and leachates on methane production from anaerobic digestion of sludge and identification of key components - Xinying Wang; Yan Zhang; Yanping Zhao; Lei Zhang; Xuxiang Zhang (Journal of Hazardous Materials, 2023)

A negative-response strain sensor towards wearable microclimate changes for body area sensing networks - Jing Liu; Junze Zhang; Zeyu Zhao; Yanping Liu; Wai Cheong Tam; Zhaozhu Zheng; Xiaoqin Wang; Yuling Li; Zekun Liu; Yi Li; Gang Li (Chemical Engineering Journal, 2023)

Genetic characteristics and growth patterns of the hybrid grouper derived from the hybridization of Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male) - Liu Cao; Pan Chen; Xingrong Hou; Jun Ma; Ning Yang; Yanping Xu; Yanjin Zhang; Anqi Zhao; Jiyuan Zhang; Xinyu Li; Hai Huang (Journal of Fish Biology, 2023)
Hybridization is one of the primary methods used to cultivate farmed grouper species. The hybrid grouper derived from crossing Epinephelus fuscoguttatus (♀) and E. polyphekadion (♂) exhibits growth superiority over its parents. The genetic characteristics and growth patterns of the hybrid grouper have not yet been defined. This study confirms the ploidy level of the hybrid grouper (2 n = 48) using chromosome count analysis and flow cytometry. The 5S rDNA family was used to evaluate genetic diversity. Only one 5S class (~400 bp) was detected in the hybrid grouper, which could be used to distinguish between two different types based on nucleotide sequences, likely representing homologous unit classes from the female and male parental species. Growth patterns of 5–8‐month‐old hybrid groupers were also monitored. In this phase, a positive allometric growth pattern in body mass with total length was found. Body height and body mass were significantly correlated based on correlation and path coefficient, suggesting that body height could serve as an excellent index to increase body mass. These results aid our understanding of the genetic evolution of the hybrid grouper and inform the development of improved rearing techniques.

MnOx@N-doped carbon nanosheets derived from Mn-MOFs and g-C3N4 for peroxymonosulfate activation: Electron-rich Mn center induced by N doping - Yue Zhao; Xiaohui Zhan; Yanping Sun; He Wang; Lei Chen; Junyan Liu; Huixiang Shi (Chemosphere, 2023)

Large-flake graphene-modified biochar for the removal of bisphenol S from water: rapid oxygen escape mechanism for synthesis and improved adsorption performance - Yurong Gao; Zheng Fang; Wenhui Lin; Hanbo Chen; Amit Bhatnagar; Jianhong Li; Yanhai Xie; Yanping Bao; Junfeng Chen; Hongting Zhao; Jun Meng; Wenfu Chen; et al. (Environmental Pollution, 2023)

S-scheme MIL-101(Fe) octahedrons modified Bi2WO6 microspheres for photocatalytic decontamination of Cr(VI) and tetracycline hydrochloride: Synergistic insights, reaction pathways, and toxicity analysis - Shijie Li; Chunchun Wang; Yanping Liu; Yazi Liu; Mingjie Cai; Wei Zhao; Xiaoguang Duan (Chemical Engineering Journal, 2023)

Novel genome sequence of Chinese cavefish ( Triplophysa rosa ) reveals pervasive relaxation of natural selection in cavefish genomes - Qingyuan Zhao; Feng Shao; Yanping Li; Soojin V. Yi; Zuogang Peng (Molecular Ecology, 2022)
All cavefishes, living exclusively in caves across the globe, exhibit similar phenotypic traits, including the characteristic loss of eyes. To understand whether such phenotypic convergence shares similar genomic bases, here we investigated genome‐wide evolutionary signatures of cavefish phenotypes by comparing whole‐genome sequences of three pairs of cavefishes and their surface fish relatives. Notably, we newly sequenced and generated a whole‐genome assembly of the Chinese cavefish Triplophysa rosa . Our comparative analyses revealed several shared features of cavefish genome evolution. Cavefishes had lower mutation rates than their surface fish relatives. In contrast, the ratio of nonsynonymous to synonymous substitutions ( ω ) was significantly elevated in cavefishes compared to in surface fishes, consistent with the relaxation of purifying selection. In addition, cavefish genomes had an increased mutational load, including mutations that alter protein hydrophobicity profiles, which were considered harmful. Interestingly, however, we found no overlap in positively selected genes among different cavefish lineages, indicating that the phenotypic convergence in cavefishes was not caused by positive selection of the same sets of genes. Analyses of previously identified candidate genes associated with cave phenotypes supported this conclusion. Genes belonging to the lipid metabolism functional ontology were under relaxed purifying selection in all cavefish genomes, which may be associated with the nutrient‐poor habitat of cavefishes. Our work reveals previously uncharacterized patterns of cavefish genome evolution and provides comparative insights into the evolution of cave‐associated phenotypic traits.

Genomic distribution of signal transducer and activator of transcription (STAT) family in colorectal cancer - Yanping Hu; Yifen Shen; Yang Zhao; Ying Tang; Chao Liu; Yongchun Gu; Tao Yang; Yihang Shen (Human Cell, 2022)

Gene–environment interaction between circadian clock gene polymorphisms and job stress on the risk of sleep disturbances - Yuxi Wang; Min Zhao; Peixin Li; Chuancheng Wu; Yanping Lv; Yu Jiang (Psychopharmacology, 2022)

Automatic identification of harmful algae based on multiple convolutional neural networks and transfer learning - Mengyu Yang; Wensi Wang; Qiang Gao; Chen Zhao; Caole Li; Xiangfei Yang; Jiaxi Li; Xiaoguang Li; Jianglong Cui; Liting Zhang; Yanping Ji; Shuqin Geng (Environmental Science and Pollution Research, 2022)

Fungal dynamic changes in naturally fermented ‘Kyoho’ grape juice - Wenjuan Zhao; Zhiming Zhang; Yuhong Gao; Xiaozhen Liu; Chaojin Du; Fuxian Ma; Sujie Wang; Wanyuan Shi; Yanping Yang; Ruyou Deng; Hanyao Zhang (Archives of Microbiology, 2022)

Sequencing and comparative analysis of chloroplast genomes of three medicinal plants: Gentiana manshurica, G. scabra and G. triflora - Rong Zhao; Shuyue Yin; Jianing Xue; Chang Liu; Yanping Xing; Haibo Yin; Xue Ren; Jixiang Chen; Dingding Jia (Physiology and Molecular Biology of Plants, 2022)

Biomonitoring and phytoremediation potential of the leaves, bark, and branch bark of street trees for heavy metal pollution in urban areas - Yanping Liu; Xiulian Zhao; Ruiming Liu; Jinxing Zhou; Zeping Jiang (Environmental Monitoring and Assessment, 2022)

The expression and interaction proteins analysis of BjuFKF1/LKP2 in B. juncea - Jing Zeng; Anran Wu; Yuemin Yang; Liang Zhao; Li Chen; Chuanqi Wang; Xin Yang; Yanping Chen; Shiyan Liu; Pei Luo; Junli Wang (Molecular Genetics and Genomics, 2022)

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Dynamic sulfur–iron cycle promoted phosphorus mobilization in sediments driven by the algae decomposition - Siyuan Zhang; Yanping Zhao; Chuanqiao Zhou; Haixin Duan; Guoxiang Wang (Ecotoxicology, 2021)

Insight into the Interaction Between Microplastics and Microorganisms Based on a Bibliometric and Visualized Analysis - Yanping Jiang; Wanjun Xia; Rui Zhao; Mengge Wang; Jinfeng Tang; Yongjun Wei (Bulletin of Environmental Contamination and Toxicology, 2021)

Molecular Cloning and Characterization of FAD6 Gene from Chia (Salvia hispanica L.) - Yufei Xue; Lejing Li; Xuemei Liu; Huanhuan Jiang; Yanping Zhao; Songzhen Wei; Na Lin; Yourong Chai (Biochemical Genetics, 2021)

Isolation and evaluation of the biocontrol potential of Talaromyces spp. against rice sheath blight guided by soil microbiome - Aqleem Abbas; Yanping Fu; Zheng Qu; Huizhang Zhao; Yongjian Sun; Yang Lin; Jiatao Xie; Jiasen Cheng; Daohong Jiang (Environmental Microbiology, 2021)
Summary Rice sheath blight caused by Rhizoctonia solani is the major disease of rice that seriously threatens food security worldwide. Efficient and eco‐friendly biological approaches are urgently needed since no resistant cultivars are available. In this study, fallow and paddy soils were initially subjected to microbiome analyses, and the results showed that Talaromyces spp. were significantly more abundant in the paddy soil, while Trichoderma spp. were more abundant in the fallow soil, suggesting that Talaromyces spp. could live and survive better in the paddy soil. Five Talaromyces isolates, namely, TF‐04, TF‐03, TF‐02, TF‐01 and TA‐02, were isolated from the paddy soil using sclerotia of R . solani as baits and were further evaluated for their activity against rice sheath blight. These isolates efficiently parasitized the hyphae and rotted the sclerotia even at higher water contents in the sterilized sand and the soil. Isolate TF‐04 significantly promoted rice growth, reduced the severity of rice sheath blight and increased the rice yield under outdoor conditions. Defence‐related genes were upregulated and enzyme activities were enhanced in rice treated with isolate TF‐04. Our research supplies a microbiome‐guided approach to screen biological control agents and provides Talaromyces isolates to biologically control rice sheath blight.

LncRNA TRHDE-AS1 inhibit the scar fibroblasts proliferation via miR-181a-5p/PTEN axis - Yanping Wei; Tingting Wang; Ningning Zhang; Yunyun Ma; Siji Shi; Ruxing Zhang; Xianzhao Zheng; Lindong Zhao (Journal of Molecular Histology, 2021)
Hypertrophic scar (HS), a fibroproliferative disorder caused by abnormal wound healing after skin injury, which is characterized by excessive deposition of extracellular matrix and invasive growth of fibroblasts. Recent studies have shown that some non-coding RNA implicated the formation of HS, but the mechanism remains unclear. In this study, we found that lncRNA TRHDE-AS1 was downregulated in HS tissues and HSFs, and the level of lncRNA TRHDE-AS1 negatively correlated with the level of miR-181a-5p in HS tissue and HSFs. Overexpressed lncRNA TRHDE-AS1 significantly suppressed miR-181a-5p level, while promoted HSFs apoptosis and inhibited HSFs proliferation. Further study shown that PTEN was a direct target of miR-181a-5p, and lncRNA TRHDE-AS1 served as a molecular sponge for miR-181a-5p to regulate the expression of PTEN. Overexpression of PTEN could eliminate lncRNA TRHDE-AS1-mediated proliferation suppression of HSFs. In conclusion, our study suggested that lncRNA TRHDE-AS1/miR-181a-5p/PTEN axis plays an important role in promoting hypertrophic scar formation, which may be effectively used as a therapeutic target for hypertrophic scar treatment.

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Clinical features and prognostic factors of patients with COVID-19 in Henan Province, China - Qianqian Zhang; Zheng Wang; Yanping Lv; Jiang Zhao; Qiang Dang; Dongfeng Xu; Dongxiang Zhao; Haiyang Liu; Ziqi Wang; Xingru Zhao; Zhiwei Xu; Xiaoju Zhang (Human Cell, 2021)

Contamination, distribution, and risk assessment of antibiotics in the urban surface water of the Pearl River in Guangzhou, South China - Chang Wang; Yanping Zhao; Shuang Liu; Qin Xiao; Weixin Liang; Yumei Song (Environmental Monitoring and Assessment, 2021)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

The Diversity of Associated Microorganisms in Different Organs and Rhizospheric Soil of Arctium lappa L. - Yanping Xing; Yanyun Yang; Liang Xu; Ning Hao; Rong Zhao; Jiahao Wang; Shengnan Li; Dachuan Zhang; Tingting Zhang; Tingguo Kang (Current Microbiology, 2020)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

Comparative physiological and metabolomic analyses reveal natural variations of tulip in response to storage temperatures - Yanping Wang; Huimin Zhao; Yaping Wang; Siyuan Yu; Yuchao Zheng; Wen’en Wang; Zhulong Chan (Planta, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Identification and molecular characterization of Serratia marcescens phages vB_SmaA_2050H1 and vB_SmaM_2050HW - Changyu Tian; Jiangtao Zhao; Zheng Zhang; Xiao Chen; Xiao Wei; Huan Li; Weishi Lin; Yuehua Ke; Lingfei Hu; Aimin Jiang; Ruo Feng; Wenhui Yang; et al. (Archives of Virology, 2019)

The importance of accounting for imperfect detection when estimating functional and phylogenetic community structure - Xingfeng Si; Marc W. Cadotte; Yuhao Zhao; Haonan Zhou; Di Zeng; Jiaqi Li; Tinghao Jin; Peng Ren; Yanping Wang; Ping Ding; Morgan W. Tingley (Ecology, 2018)
Incorporating imperfect detection when estimating species richness has become commonplace in the past decade. However, the question of how imperfect detection of species affects estimates of functional and phylogenetic community structure remains untested. We used long‐term counts of breeding bird species that were detected at least once on islands in a land‐bridge island system, and employed multi‐species occupancy models to assess the effects of imperfect detection of species on estimates of bird diversity and community structure by incorporating species traits and phylogenies. Our results showed that taxonomic, functional, and phylogenetic diversity were all underestimated significantly as a result of species’ imperfect detection, with taxonomic diversity showing the greatest bias. The functional and phylogenetic structure calculated from observed communities were both more clustered than those from the detection‐corrected communities due to missed distinct species. The discrepancy between observed and estimated diversity differed according to the measure of biodiversity employed. Our study demonstrates the importance of accounting for species’ imperfect detection in biodiversity studies, especially for functional and phylogenetic community ecology, and when attempting to infer community assembly processes. With datasets that allow for detection‐corrected community structure, we can better estimate diversity and infer the underlying mechanisms that structure community assembly, and thus make reliable management decisions for the conservation of biodiversity.

Anti-proliferation effects of ethanolic extracts from Sophora moorcroftiana seeds on human hepatocarcinoma HepG2 cell line - Gang Su; Wenke Yang; Wenbo Meng; Qionghui Wu; Yanping Luo; Xingming Ma; Shen Zhao; Xiaodong Xie; Guang-Qin Guo (Natural Product Research, 2018)

Enhanced a novel β-agarase production in recombinant Escherichia coli BL21 (DE3) through induction mode optimization and glycerol feeding strategy - Zhuhua Chan; Xinglin Chen; Yanping Hou; Boliang Gao; Chungui Zhao; Suping Yang; Runying Zeng (Acta Oceanologica Sinica, 2018)

Recent land cover changes and sensitivity of the model simulations to various land cover datasets for China - Liang Chen; Zhuguo Ma; Rezaul Mahmood; Tianbao Zhao; Zhenhua Li; Yanping Li (Meteorology and Atmospheric Physics, 2017)

Tolerance and Removal Mechanisms of Heavy Metals by Fungus Pleurotus ostreatus Haas - Suqin Yang; Xiaoxue Sun; Yanping Shen; Cheng Chang; Erhui Guo; Guixiao La; Yong Zhao; Xuanzhen Li (Water, Air, & Soil Pollution, 2017)

Improving N management through intercropping alleviates the inhibitory effect of mineral N on nodulation in pea - Falong Hu; Cai Zhao; Fuxue Feng; Qiang Chai; Yanping Mu; Yan Zhang (Plant and Soil, 2017)

Changes in endogenous hormones and H2O2 burst during shoot organogenesis in TDZ-treated Saussurea involucrate explants - Bin Guo; Wei He; Yan Zhao; Yandi Wu; Yanping Fu; Juan Guo; Yahui Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Expression of lycopene biosynthesis genes fused in line with Shine-Dalgarno sequences improves the stress-tolerance of Lactococcus lactis - Xiangrong Dong; Yanping Wang; Fengyuan Yang; Shanshan Zhao; Bing Tian; Tao Li (Biotechnology Letters, 2017)

Cyclic utilization of HP-β-CD in the bioconversion of cortisone acetate by Arthrobacter simplex - Yanbing Shen; Fang Wang; Yanping Wang; Qing Zhao; Min Wang (Biotechnology Letters, 2016)

Detection of virus in CSF from the cases with meningoencephalitis by next-generation sequencing - Hongzhi Guan; Ao Shen; Xia Lv; Xunzhe Yang; Haitao Ren; Yanhuan Zhao; Yinxin Zhang; Yanping Gong; Peixiang Ni; Honglong Wu; Yicheng Zhu; Liying Cui (Journal of NeuroVirology, 2016)

Isolation of a new carboline alkaloid from Trigonostemon lii - Hongmei Yang; Yanping Luo; Hongmei Zhao; Jichun Wu; Yegao Chen (Natural Product Research, 2016)

Insights into tetracycline adsorption onto kaolinite and montmorillonite: experiments and modeling - Yanping Zhao; Xueyuan Gu; Shiyin Li; Ruiming Han; Guoxiang Wang (Environmental Science and Pollution Research, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Joint toxicity of tetracycline with copper(II) and cadmium(II) to Vibrio fischeri: effect of complexation reaction - Fei Tong; Yanping Zhao; Xueyuan Gu; Cheng Gu; Charles C.C. Lee (Ecotoxicology, 2015)

Intake of fruit and vegetables and risk of bladder cancer: a dose–response meta-analysis of observational studies - Baodong Yao; Yujie Yan; Xianwu Ye; Hong Fang; Huilin Xu; Yinan Liu; Sheran Li; Yanping Zhao (Cancer Causes & Control, 2014)

Composition and spectroscopic characteristics of dissolved organic matter extracted from the sediment of Erhai Lake in China - Yanping Li; Shengrui Wang; Li Zhang; Haichao Zhao; Lixin Jiao; Yali Zhao; Xiaosong He (Journal of Soils and Sediments, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Association study of common variations of FBN1 gene and essential hypertension in Han Chinese population - Jinfeng Chen; Song Yang; Xianghai Zhao; Jiahui Shen; Hairu Wang; Yanchun Chen; Yanni Ji; Wen Wang; Wei Zhou; Xuecai Wang; Junming Tang; Xiangfeng Lu; et al. (Molecular Biology Reports, 2014)

Therapy with Astragalus polysaccharides rescues lipotoxic cardiomyopathy in MHC-PPARα mice - Wei Chen; Wenjie Chen; Yanping Xia; Xuelan Zhao; Hao Wang; Maohua Yu; Yiming Li; Hongying Ye; Yu Zhang (Molecular Biology Reports, 2013)

Identification and analysis of the gene cluster involved in biosynthesis of paenibactin, a catecholate siderophore produced by Paenibacillus elgii B69 - Yanping Wen; Xuechang Wu; Yi Teng; Chaodong Qian; Zhajun Zhan; Yuhua Zhao; Ou Li (Environmental Microbiology, 2011)
Summary Bacteria belonging to the genus Paenibacillus are recognized as rich sources of bioactive natural products. To date, there are few characterized siderophores from this genus. Here, through genome analysis, we identified a non‐ribosomal peptide biosynthetic gene cluster ( pae ) responsible for siderophore assembly in Paenibacillus elgii B69. The 12.8 kb gene cluster comprises six open reading frames encoding proteins similar to the components of the bacillibactin biosynthetic machinery and bacillibactin esterase. To examine the product of the pae gene cluster, we cultured P. elgii B69 in iron‐deficient medium for siderophore expression. A novel siderophore structurally similar to bacillibactin, designated paenibactin, was purified and characterized. Its structure was determined as a cyclic trimeric lactone of 2,3‐dihydroxybenzoyl‐alanine‐threonine. The involvement of the pae gene cluster in paenibactin biosynthesis was confirmed by the biochemical assay of adenylation domain specificity. Furthermore, we demonstrated that the pae gene cluster evolves from an ancestral bacillibactin biosynthetic gene cluster via sequence and phylogenetic analyses. The structural difference between paenibactin and bacillibactin may stem from a mutation‐induced change in the adenylation domain specificity. Based on these findings and published models for bacillibactin, we proposed models for paenibactin biosynthesis, ferric–paenibactin uptake and paenibactin‐bounded iron release.

Tetracycline adsorption on kaolinite: pH, metal cations and humic acid effects - Yanping Zhao; Jinju Geng; Xiaorong Wang; Xueyuan Gu; Shixiang Gao (Ecotoxicology, 2011)

Caveolin-1 restoration by cholesterol enhances the inhibitory effect of simvastatin on arginine vasopressin-induced cardiac fibroblasts proliferation - Shaowei Liu; Yanping He; Yufeng Dou; Haichang Wang; Ling Tao; Lianyou Zhao; Fujun Shang; Hui Liu (Molecular and Cellular Biochemistry, 2009)

Preparation and some properties of cholesterol oxidase from Rhodococcus sp. R14-2 - Chengtao Wang; Yanping Cao; Baoguo Sun; Baoping Ji; M. J. Robert Nout; Ji Wang; Yonghuan Zhao (World Journal of Microbiology and Biotechnology, 2008)

Induced expression of oryzain α gene encoding a cysteine proteinase under stress conditions - Yanping Fu; Wensheng Zhao; Youliang Peng (Journal of Plant Research, 2007)